Pengelolaan Kawasan Perbatasan Motaain Dalam Upaya Pengentasan Kemiskinan di Desa Silawan Kabupaten Belu - Yulianto Dato Alin; Fransina W. Ballo; Maria Indriani Hewe Tiwu (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aims to find out the strategy of utilizing the management of the Motaain border area in an effort to alleviate poverty in Silawan Village. This research was conducted at the Motaain Border of Silawan Village, Belu Regency using primary and secondary data. The results of this study show how the SO (Strength-Opportunity) strategy uses adequate natural resources, locations close to PLBN and the existence of animal feed factories by taking advantage of opportunities such as in the agriculture and plantation, tourism and trade and logistics sectors to increase the economic activities of the local community and be able to reduce poverty in Silawan Village. The obstacles that are often faced in poverty alleviation in Silawan Village are limited resources, economic activities that occur are more dominant in the outside community and security that is still weak so that smuggling often occurs. The location close to PLBN and the existence of a animal feed factory are expected to provide alternative solutions for farmers to manage agricultural products into animal feed and revive the culture of livestock in border areas.